Global Warming and Climate Change: Science and Politics - Ollier, Cliff (Quaestiones Geographicae, 2013)
The threat of dangerous climate change from anthropogenic global warming has decreased. Global temperature rose from 1975 to 1998, but since then has levelled off. Sea level is now rising at about 1.5mm per year based on tide gauges, and satellite data suggests it may even be falling. Coral islands once allegedly threatened by drowning have actually increased in area. Ice caps cannot possibly slide into the sea (the alarmist model) because they occupy kilometres-deep basins extending below sea level. Deep ice cores show a succession of annual layers of snow accumulation back to 760,000 years and in all that time never melted, despite times when the temperature was higher than it is today. Sea ice shows no change in 30 years in the Arctic. Emphasis on the greenhouse effect stresses radiation and usually leads to neglect of important factors like convection. Water is the main greenhouse gas. The CO2 in the ocean and the atmosphere are in equilibrium: if we could remove CO2 from the atmosphere the ocean would give out more to restore the balance. Increasing CO2 might make the ocean less alkaline but never acid. The sun is now seen as the major control of climate, but not through greenhouse gases. There is a very good correlation of sunspots and climate. Solar cycles provide a basis for prediction. Solar Cycle 24 has started and we can expect serious cooling. Many think that political decisions about climate are based on scientific predictions but what politicians get are projections based on computer models. The UN’s main adviser, the IPCC, uses adjusted data for the input, their models and codes remain secret, and they do not accept responsibility for their projections.